2018
DOI: 10.1007/s12325-018-0718-9
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter, Randomized, Controlled Study Comparing Tafluprost/Timolol Fixed Combination with Latanoprost/Timolol Fixed Combination in Primary Open-Angle Glaucoma and Ocular Hypertension

Abstract: Santen Pharmaceutical Co., Ltd., Osaka, Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
4
0
3
Order By: Relevance
“…A further study in which patients were switched from LTFC to a fixed combination of tafluprost/timolol (TTFC) found no significant difference in IOP after the switch. 7 This result was similar to that of the meta-analysis, which found no difference in IOP-lowering efficacy between latanoprost and tafluprost and a significant decrease in reports of eye irritation and eye pain after switching to TTFC. 6 Another meta-analysis reported that the IOPlowering efficacy of a fixed combination of bimatoprost/timolol was better than that of LTFC and TTFC and that conjunctival hyperemia was less common with LTFC than with the fixed combination of bimatoprost/timolol.…”
Section: Discussionsupporting
confidence: 87%
“…A further study in which patients were switched from LTFC to a fixed combination of tafluprost/timolol (TTFC) found no significant difference in IOP after the switch. 7 This result was similar to that of the meta-analysis, which found no difference in IOP-lowering efficacy between latanoprost and tafluprost and a significant decrease in reports of eye irritation and eye pain after switching to TTFC. 6 Another meta-analysis reported that the IOPlowering efficacy of a fixed combination of bimatoprost/timolol was better than that of LTFC and TTFC and that conjunctival hyperemia was less common with LTFC than with the fixed combination of bimatoprost/timolol.…”
Section: Discussionsupporting
confidence: 87%
“…However, according to previous reports, 2% dorzolamide and 1% brinzolamide share similar IOP-lowering efficacies [11], and those of 0.005% latanoprost and 0.0015% tafluprost are comparable as well [12][13][14]. Suzuki et al [15] reported randomized controlled study results comparing the efficacy and safety of a tafluprost/timolol fixed combination and a latanoprost/timolol fixed combination. In their study, there were no significant differences observed between the two groups in terms of IOP, superficial punctate keratopathy score, tear breakup time, or hyperemia score after 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Second, our meta-analysis did not include all the different fixed combinations. An open-label study reported the difference between a tafluprost/timolol fixed combination and LTFC, with 131 patients who were followed up for three months [12]. This study found that the IOP before and 4-6 hours after administration were not significantly different.…”
Section: Discussionmentioning
confidence: 86%
“…We then screened each of these 19 articles for their content and methodological qualities. Based on our thorough screening, we excluded one article because LTFC was used only as a run-in treatment before the randomization [11] and another article because it is an open-label study [12]. As a result, a total of 17 articles describing 17 clinical trials that addressed LTFC versus other anti-glaucoma fixed combinations for POAG and OHT patients were included in the systematic review, and 16 of these articles were included in the meta-analysis.…”
Section: Search For Relevant Studiesmentioning
confidence: 99%